Aminoglycoside-Modifying Enzymes Are Sufficient to Make Pseudomonas aeruginosa Clinically Resistant to Key Antibiotics - Aswin Thacharodi; Iain L. Lamont (MDPI AG, 2022)
Aminoglycosides are widely used to treat infections of Pseudomonas aeruginosa. Genes encoding aminoglycoside-modifying enzymes (AMEs), acquired by horizontal gene transfer, are commonly associated with aminoglycoside resistance, but their effects have not been quantified. The aim of this research was to determine the extent to which AMEs increase the antibiotic tolerance of P. aeruginosa. Bioinformatics analysis identified AME-encoding genes in 48 out of 619 clinical isolates of P. aeruginosa, with ant(2')-Ia and aac(6')-Ib3, which are associated with tobramcyin and gentamicin resistance, being the most common. These genes and aph(3')-VIa (amikacin resistance) were deleted from antibiotic-resistant strains. Antibiotic minimum inhibitory concentrations (MICs) were reduced by up to 64-fold, making the mutated bacteria antibiotic-sensitive in several cases. Introduction of the same genes into four antibiotic-susceptible P. aeruginosa strains increased the MIC by up to 128-fold, making the bacteria antibiotic-resistant in all cases. The cloned genes also increased the MIC in mutants lacking the MexXY-OprM efflux pump, which is an important contributor to aminoglycoside resistance, demonstrating that AMEs and this efflux pump act independently in determining levels of aminoglycoside tolerance. Quantification of the effects of AMEs on antibiotic susceptibility demonstrates the large effect that these enzymes have on antibiotic resistance.